Scattering from surface waves on finite FSS. - Munk, B.A (IEEE Transactions on antennas and propagation)
This paper discusses the presence of surface waves on periodic structures in general and on frequency selective surfaces (FSS) in particular. While certain types of surface waves can exist on infinite as well as finite periodic structures, this investigation centers around the types that can exist only on finite FSS. Radiation caused by these surface waves may lead to a significant scattering increase in the backscatter as well as the bistatic directions. Thus, this paper is of both theoretical and practical interest